Relationship between preoperative high arterial blood lactate level and delirium after deep brain stimulation surgery in Parkinson’s disease - Lu, Wenbin; Rao, Miaomiao; Lu, Liangliang; Li, Panpan; Dou, Xiaorong; Bian, Jinjun; Deng, Xiaoming (Frontiers in Aging, 2025)
Introduction: We performed the retrospective study to investigate the relationship between preoperative arterial blood lactate level and postoperative delirium (POD) in Parkinson's disease (PD) patients undergoing deep brain stimulation (DBS) surgery.Methods: Perioperative data of patients undergoing DBS surgery under total intravenous anesthesia were collected in the study. In addition, mini-mental state exam score for assessing cognitive function and confusion assessment method for assessing perioperative delirium in the PD patients were collected. The relationship between preoperative lactate level and POD was analyzed using binary logistic regression analysis.Results: A total of 156 patients were included, of whom 29 (17.6%) patients developed POD. Multivariable logistic regression analysis showed that preoperative lactate level was independently associated with POD regarding of continuous variable [odds ratio (OR) = 12.46, 95% confidence interval (CI)=3.12–49.71, P<0.001] or categorical variable (OR= 3.58, 95% CI =1.20–10.65, P=0.022 for lactate≥1.41). Receiver operating characteristic curve analysis showed that preoperative arterial blood lactate level was a significant predictive biomarker for POD, with an area under the curve of 0.708(95%CI=0.606–0.809, P<0.05). Subgroup analysis indicated that high preoperative lactate levels were an independent risk factor for delirium after DBS surgery (OR=10.71,95%CI=1.17–97.87, P=0.036) in female Parkinson's disease patients.Discussion: Preoperative high level of lactate is an independent factor for delirium after DBS surgery in patients with Parkinson's disease.